AWARENESS OF BREAST SELF EXAMINATION AMONG SECONDARY SCHOOL GIRLS (15-17 YEARS) BETWEEN RURAL AND URBAN AREAS OF EBONYI STATE. - Shirley, Akpovona Ochuko; Okoronkwo, C. A, Okoronkwo (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The aim of this study was to investigate the level of awareness of breast self-examination among secondary school girls (15-17 years old) in Ebonyi State's rural and urban districts. The study was designed as a cross sectional survey of female secondary school students using questionnaire for data collection. The study population was from a secondary school (1000 females), 500 females were from rural areas of Ebonyi State while 500 females were from urban areas of Ebonyi State. Data obtained was analysed using chi square Pearson correlation coefficient (r) which is one of the tools in International Business Machine Statistical Package for Social Science (IBMSPSS) version 25. From the results obtained, awareness of breast self-examination for the urban subjects were reported to be 62.3% while for the rural subjects, it was reported to be 37.7%. The major source of awareness of breast self-examination was from health workers for urban dwellers and television for rural dwellers. In conclusion, disparity in the awareness of breast self-examination between urban and rural secondary school girls (age 15-17) in Ebonyi State was found and thus it is important to create awareness of BSE among young girls most especially the rural area dwellers.